Research on Energy Saving of Dual-loop Coupled Refrigerator with Two-stage Throttling - 王亚聪; 唐黎明; 邬晗晖; 陈光明; 陈琪 (Zhileng xuebao)
When a dual-loop coupled refrigerator operates in a coupled state, the condensation pressure of the freezing loop decreases, such that the refrigerant outlet of the condenser is not completely condensed. Hence, the cooling capacity provided by the freezing loop is used to treat the refrigerant that is not completely condensed. It is therefore difficult for the system to take full advantage of the energy-saving ability of the design. To solve this problem, we propose a dual-loop coupled system with two-stage throttling. By adding a throttling expansion device between the freezing condenser and coupled subcooler, the system can operate stably. In this study, the refrigerant is R600a. Under the conditions of ambient temperature of 25 °C and freezer temperature of ?18 °C, we simulated the operating state of the system using Matlab, which was validated by an experimental device. The research results show that the system can maintain stability in both independent and coupled operations when the system works under the design conditions, and the coefficient of performance (COP) of the coupled operation is approximately 9% higher than that of the independent operation.